PENGARUH KOMPETENSI, KOMPENSASI DAN KINERJA TERHADAP PENGEMBANGAN KARIER DI PT SEMEN BATURAJA - Yunus, Muhammad; Zamzam, Fakhry; Hildayanti, Siti Komariah (KHOZANA: Journal of Islamic Economic and Banking, 2020)
The purpose of this study is specifically to obtain the results of the analysis of factors that affect employee career development such as competency, compensation and performance variables for employees of the Marketing Directorate of PT Semen Baturaja (Persero) Tbk, either partially or simultaneously. This thesis research uses a quantitative approach with a confirmative survey method that is descriptive and verification. Where verification research is carried out to test the hypothesis, while descriptive to describe the variables studied. Meanwhile, based on the objective, this research uses descriptive and experimental research methods. The population of this study were 112 employees at the Marketing Directorate of PT Semen Baturaja (Persero) Tbk who as a whole were sampled. Data processing using analysis tools SPSS version 25. Testing data using the t test, that the competency variable proves that partially competence does not have a positive and significant effect on career development with a tcount of -0.145 where <of t table (0.05, n-2) 1.98177 and the significance value (Sig) 0.885 where> from the probability of 0.05; then partially compensation has a positive and significant effect on Career Development with a tcount value of 6.318 which is greater than t table (0.05, n-2) 1.98177 and a significance value (Sig) 0.000 which is smaller than the probability 0.05 and Partial performance also has a positive and significant effect on career development with a t-count value of 3.588 which is greater than t-table (0.05, n-2) 1.98177 and a significance value (Sig) of 0.001 which is smaller than the probability of 0.05. The results of the analysis of the F test of competency, compensation and performance variables simultaneously get an F value of 57.785 where this value is greater than the F-table value (2, n-2) which is 2.69 and a significance value (Sig) of 0.000 which is smaller than the probability of 0, 05. The results of the analysis prove that simultaneously competence, compensation and performance have a positive and significant effect on career development.